IMPACT OF STOCK PRICES AND GCG ON FIRM VALUE: EVIDENCE FROM INDONESIAN REAL ESTATE COMPANIES - Salsyadillah, Meilani; Fadhilah, Ash Shoffi Hana; Habibi, Pahman (Univesitas Muhammadiyah Tangerang, 2025)
This study investigates the impact of stock prices and Good Corporate Governance (GCG) on company value in the property and real estate sector listed on the Indonesia Stock Exchange, an industry pivotal to economic growth yet prone to market volatility and governance deficiencies. Given Indonesia’s rising urbanization and investment inflows, understanding value drivers in this sector is crucial for sustainable development and investor protection. Using panel data regression from 2020–2023, we analyze stock price, audit committee size, managerial ownership, board of directors, and independent board of commissioners as key determinants. Results reveal that stock price and managerial ownership exert a significant positive effect on firm value, indicating market efficiency and effective alignment of managerial incentives. However, audit committee, board of directors, and independent commissioners show no significant influence, suggesting structural weaknesses in oversight and decision-making independence. Collectively, all variables significantly enhance firm value, emphasizing the interplay between market signals and governance. This study contributes to the literature by offering timely empirical evidence from an emerging market with evolving regulatory frameworks. Its novelty lies in integrating market-based performance (stock price) with multidimensional GCG indicators in the Indonesian real estate context—underexplored in prior research. Furthermore, it provides policy implications for regulators to strengthen board independence and monitoring mechanisms to improve corporate accountability and long-term value creation.